2017
DOI: 10.1016/j.ijforecast.2015.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating expert advice in forecasting: Users’ reactions to presumed vs. experienced credibility

Abstract: In expert knowledge elicitation (EKE) for forecasting, the perceived credibility of an expert is likely to affect the weighting attached to their advice. Four experiments have investigated the extent to which the implicit weighting depends on the advisor's experienced (reflecting the accuracy of their past forecasts), or presumed (based on their status) credibility. Compared to a control group, advice from a source with a high experienced credibility received a greater weighting, but having a low level of expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 71 publications
(89 reference statements)
1
7
0
Order By: Relevance
“…Indeed, this behavior‐belief (in)congruity is another dimension of algorithmic advice taking that is under‐studied, and we believe that this may lead to false generalizations about the persuasive impact of algorithms. Past studies have found that statements or presumptions of trust in advisors do not necessarily correspond how influential their advice is in belief revision (Goodwin et al, 2013; Önkal et al, 2017). More specifically, higher levels of trust did not meaningfully increase persuasiveness compared to controls, though lower levels of trust did, albeit slightly.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, this behavior‐belief (in)congruity is another dimension of algorithmic advice taking that is under‐studied, and we believe that this may lead to false generalizations about the persuasive impact of algorithms. Past studies have found that statements or presumptions of trust in advisors do not necessarily correspond how influential their advice is in belief revision (Goodwin et al, 2013; Önkal et al, 2017). More specifically, higher levels of trust did not meaningfully increase persuasiveness compared to controls, though lower levels of trust did, albeit slightly.…”
Section: Introductionmentioning
confidence: 99%
“…One intuitive research question that arises is how humans take the provided advice and use it to update their belief. On a human-to-human basis, Önkal et al [212] and Ayton & Önkal [213] investigated empirically the driving factors in using recommendations and advice. The authors assess whether experienced or presumed credibility has more impact on judges' readiness to use advice.…”
Section: Human Advice Taking and Belief Updatingmentioning
confidence: 99%
“…the credibility purveyed through the status of the advice giver, plays the biggest role in judgement adoption. Önkal et al [212] showed, experimentally, that advice from a forecaster with high experienced credibility received a higher weight, and a lower level of credibility did not affect the weighting negatively. High presumed credibility in turn did not result in an allocation of more weight to the model, although low presumed credibility resulted in a decrease.…”
Section: Human Advice Taking and Belief Updatingmentioning
confidence: 99%
“…Previous research on advice-taking explored various cues that people use to infer competence [ 31 , 32 ]. In this paper, we focused on two of them: expertise and the outcome of the decision.…”
Section: Introductionmentioning
confidence: 99%
“…From early childhood human beings are attuned to others’ expertise [ 31 39 ]. “Says who?” is what we immediately think when exposed to someone else’s opinion [ 40 ].…”
Section: Introductionmentioning
confidence: 99%